Enhancing Young Agripreneurs’ Capacity: Shaping a Sustainable Generation of Horticultural Farmers - Sodik Dwi Purnomo; Sri Sundari; Bagus Adhitya; Toni Suseno; Alfit Budi Prasetyo (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study examines the determinants of young agripreneur capacity in the horticultural sector of Purbalingga Regency, emphasising the moderating role of climate change—an aspect rarely integrated into previous studies that predominantly focus on the direct determinants of young farmers’ capacity. Using a Partial Least Square–Structural Equation Modeling (PLS-SEM) approach, this study analyzes the effects of farmer characteristics, external support, and the role of extension agents within a moderated structural framework. Data were collected from 100 young horticultural farmers in the villages of Kutabawa and Serang using purposive sampling. The results show that farmer characteristics (? = 0.267; p = 0.039), external support (? = 0.298; p = 0.009), and the role of extension agents (? = 0.261; p = 0.014) have positive and significant effects on agripreneur capacity, with the model explaining 46.1% of the variance (R² = 0.461). Climate change does not have a direct effect (? = 0.107; p = 0.269), but it significantly moderates the relationship between farmer characteristics and agripreneur capacity (? = 0.245; p = 0.044). However, it does not moderate the influence of external support (? = -0.189; p = 0.065) or the role of extension agents (? = 0.034; p = 0.740). These findings demonstrate that climate change functions as a conditional strengthening factor for individual-based capacity rather than as an institutional support mechanism. The study highlights that strengthening young agripreneur capacity requires prioritizing farmer characteristics, improving the effectiveness of external support, and enhancing adaptive extension services aligned with climate challenges. Contribution to Sustainable Development Goals (SDGs):SDG 8 (Economic Growth)SDG 13 (Climate Action)SDG 2 (Zero Hunger)SDG 17 (Partnerships)